Proposed Strategies to Improve Adult Asthma Management in Egypt: Expert Review and Recommendations - Hossam Hosny; Ashraf Madkour; Mohamed Hantera; Mohamed Dahy; Faten Emara; Maha Ibrahim; Tarek Safwat (Ubiquity Press, 2022)
Background: Several challenges face asthma management in Egypt, including the high percentage of uncontrolled patients, inadequate compliance, and overuse of short-acting beta-agonists (SABAs) leading to increased asthma-related morbidity and mortality. In this regard, the recent Global Initiative for Asthma (GINA) recommendations included inhaled corticosteroids containing therapy for mild asthma. Local healthcare systems and healthcare professionals (HCPs) often experience practical challenges when implementing global guidelines. Objective: The present expert review aims to outline the development of local guidelines and health policies that integrate global advances in asthma management while addressing unmet needs and challenges in Egypt. Methods: A steering committee of health policymakers and respiratory experts from the principal healthcare sectors in Egypt came together in March 2021 to develop a consent and national guideline for local asthma management, codifying the current challenges and the required elements for adequate control. The recommendations were either evidence-based or consensus-based from the clinical expertise and perspectives of the committee. Results: The committee identified vital challenges facing all chronic airway diseases with initial focus on asthma management in Egypt in diagnosis, data collection, policymaking, patients' awareness, and physicians' attitudes. In general, the committee stated that globally adapted management protocols necessitate addressing from diverse perspectives through policymakers, HCPs, and patients. Accordingly, it is vital to provide relevant education for the patient and HCPs. The recommendations emphasize key elements concerning baseline assessment, diagnosis, treatment strategy with regular review of patient progress, and compliance toward the introduced reforms. Conclusions: Full integration of these recommendations into local practice allows physicians to sustain adequate management while reducing preventable exacerbations and unnecessary burdens. The proposed strategies outline efficient patient-centered management that approaches asthma as an inflflammatory condition, encouraging health promotion and patients' compliance.